Amination strategy to boost the CO2 electroreduction current density of M–N/C single-atom catalysts to the industrial application level. Issue 4 (2nd March 2021) - Chen, Zhipeng; Zhang, Xinxin; Liu, Wei; Jiao, Mingyang; Mou, Kaiwen; Zhang, Xiangping; Liu, Licheng
Abstract : Amino-modification, as an ingenious strategy, was proposed for boosting CO2 electroreduction current density of Ni–N/C single-atom catalyst to industrial level. Abstract : Although the Faraday efficiency (FE) for CO production of single-atom catalysts immobilized on nitrogen-doped carbon supports (M–N/C) for the CO2 electrocatalytic reduction reaction (CO2 RR) is generally over 90%, M–N/C catalysts demonstrate a poor reaction current density, which is much worse than the current density at the industrial level. Herein, we first report a generalized amination strategy to significantly increase the current density for CO production of M–N/C catalysts (M = Ni, Fe, Zn). Among them, the aminated Ni single-atom catalyst achieves a remarkable CO partial current density of 450 mA cm −2 (a total current density over 500 mA cm −2 ) with a nearly 90% CO FE at a moderate overpotential of 0.89 V, and particularly CO FE can be maintained over 85% in a wide operating potential range from −0.5 V to −1.0 V. DFT calculations and experimental research demonstrate that the superior activity is attributed to enhanced adsorption energies of CO2 * and COOH* intermediates caused by the regulation of the electronic structure of the aminated catalysts. This work provides an ingenious method for significantly increasing the current density at the industrially-relevant level of single-atom catalysts for the CO2 RR.